Pemanfaatan Berbagai Jenis Pupuk Organik Hayati terhadap Produksi Bawang Merah (Allium ascalonicum L.) di Tanah Pasang Surut Tipe Luapan C Asal Banyuurip - Neni Marlina; Nurbaiti Amir; Berliana Palmasari (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Marlina et al, 2018. Utilization of Various Types of Biofertilizer on the Production of Shallots (Allium ascalonicum L.) in overflow type C Tidal Soils from Banyuurip. JLSO 7(1):74-79.Â Tidal land has considerable potential to be used as agricultural land, one of which is for shallot, but the obstacles faced in this tidal land are high soil acidity and low soil fertility. Therefore, to increase the production of onion plants can be given biological organic fertilizer. This study aimed to analyze the right type of biological organic fertilizer in increasing the production of shallots. This research was carried out at the Greenhouse in Palembang. The design used was Factorial Randomized Completely Block Design with consisted of 4 treatment factors with 6 replications for each treatment.Â The first factor was control (O0), the second factor was biofertilizer enriched with Azospirillum (O1) bacteria, the third factor was biofertilizer enriched with phosphate solvent bacteria (BPF) (O2), and the fourth factor was biofertilizers enriched with Azospirillum and BPF bacteria. The results showed that the treatment of Azospirillum and BPF-enriched biofertilizers gave the best production per hill of onion by 85.33 g.